2006
DOI: 10.5751/es-01929-110236
|View full text |Cite
|
Sign up to set email alerts
|

Companion Modeling, Conflict Resolution, and Institution Building: Sharing Irrigation Water in the Lingmuteychu Watershed, Bhutan

Abstract: We used multi-agent systems (MAS), following the companion modeling method, to facilitate water management negotiations in Bhutan. We show how this methodology helped resolve a conflict over the sharing of water resources by establishing a concrete agreement and creating an institution for collective watershed management. The conceptual model begins with a role-playing game (RPG). The stakeholders play the game, thus validating the proposed environment, the behavioral rules, and the emergent properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
17

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 11 publications
0
80
0
17
Order By: Relevance
“…Their study indicated not only a strengthening of relationships between diverse stakeholders through increased mutual trust and empathy, but also an improved understanding of the system and complex issues at play. This was also found by Gurung et al [91] who asked farmers from villages in conflict over water allocations to play a simulation game in which the farmers swapped roles for one round of the game. They found that, "the scenario with swapped roles, during which upper villagers played the role of lower villagers and vice versa, was very effective at sharing different points of view".…”
Section: Quality Of Stakeholder Relationshipsmentioning
confidence: 68%
See 1 more Smart Citation
“…Their study indicated not only a strengthening of relationships between diverse stakeholders through increased mutual trust and empathy, but also an improved understanding of the system and complex issues at play. This was also found by Gurung et al [91] who asked farmers from villages in conflict over water allocations to play a simulation game in which the farmers swapped roles for one round of the game. They found that, "the scenario with swapped roles, during which upper villagers played the role of lower villagers and vice versa, was very effective at sharing different points of view".…”
Section: Quality Of Stakeholder Relationshipsmentioning
confidence: 68%
“…One way to increase stakeholder interactions is through the involvement of stakeholders not in only the game play, but also the design and development of a game simulation. Gurung et al [91], as an example, involved their study participants in the process of developing the game they would later play, much like a collaborative modelling process. This not only helped to increase interactions, but also encouraged consensus building regarding the facts of the underlying system, as well as the development of a shared vision and goals.…”
Section: Stakeholder Interactions and The Way This Engagement Processmentioning
confidence: 99%
“…Participants simultaneously acquire not only new eco-technical knowledge but also new social skills such as the ability to understand each other's views and interests, collectively explore scenarios, negotiate, define, and commit to practical solutions. Companion Modeling has proven its capacity to help stakeholders understand, mediate, and solve social conflicts involving common pool resources in rural settings (Bousquet and Trebuil 2005, Gurung et al 2006, Daré et al 2008. Trade-offs, or synergies, and trends can thus be observed.…”
Section: Participatory Processes: Methods and Toolsmentioning
confidence: 99%
“…Such a system benefits from the participation of stakeholders in its design, especially when dealing with complex issues; this is a move from a classical modelling approach to a more participative methodology (Costanza and Ruth 1998;Van Asselt-Marjolein and Rijkens-Klomp 2002;Vennix et al 1996;Vennix 1999). The active involvement of all relevant stakeholder groups can additionally help to foster a sense of ownership of the decisión making process (Gurung et al 2006;Lynam et al 2007). …”
Section: Participatory Decisión Support Systems In Iwrmmentioning
confidence: 99%